1992
DOI: 10.1007/bf00317165
|View full text |Cite
|
Sign up to set email alerts
|

Differences in relative growth rate in 11 grasses correlate with differences in chemical composition as determined by pyrolysis mass spectrometry

Abstract: Eleven grass species varying in potential relative growth rate (RGR) were investigated for differences in chemical composition by pyrolysis mass spectrometry. The spectral data revealed correlations between RGR and the relative composition of several biopolymers. Species with a low potential RGR contained relatively more cell wall material such as lignin, hemicellulose, cellulose, polysaccharide-bound ferulic acid and hydroxyproline-rich protein, whereas species with a high potential RGR showed relatively more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 20 publications
6
57
0
1
Order By: Relevance
“…Earlier studies showed that species with a high RGR,,,.,^ eontain more cytoplasm and showed that species with a high SLM contain more chemical compounds with a high carbon concentration (Niemann et al, 1992;Van Arendonk & Poorter 1994). Our results do not show a .significant difference in carbon concentration between the fast-and slow-growing species growing with free access to nitrate (RGRmax- fig.8b).…”
Section: Carbon Concentration and Anatomymentioning
confidence: 41%
See 1 more Smart Citation
“…Earlier studies showed that species with a high RGR,,,.,^ eontain more cytoplasm and showed that species with a high SLM contain more chemical compounds with a high carbon concentration (Niemann et al, 1992;Van Arendonk & Poorter 1994). Our results do not show a .significant difference in carbon concentration between the fast-and slow-growing species growing with free access to nitrate (RGRmax- fig.8b).…”
Section: Carbon Concentration and Anatomymentioning
confidence: 41%
“…The low SLA of slowgrowing species is associated with more non-veinal sclerenchymatic cells, relatively small epidermal cells (Van Arendonk & Poorter 1994), a low leaf water content and a higli leaf mass density (Garnier & Laurent 1994;Ryser & Lambers 1995). Chemically, low SLA is associated with a comparatively high ratio of cell wall components to cytoplasmic compounds (Niemann et al 1992;Van Arendonk & Poorter 1994), which might be the cause of a higher leaf mass density.…”
Section: Introductionmentioning
confidence: 99%
“…For proteins we recently published a number of marker fragment ions [43 ] additional to specific ones such as presented before [37,39,40 ]. In the present work major changes in proteins were not found.…”
Section: Carnationmentioning
confidence: 48%
“…Interpretation of PyMS spectra Lists of specific marker fragments for the different plant polymers and other constituents have been presented before [22,37,39,40,43 ]. Therefore, only the ions mentioned in the text and those shown in the figures are mentioned, and where necessary their validity as marker ion will be discussed.…”
Section: Carnationmentioning
confidence: 99%
“…For instance, Dactylis glomerata L., a perennial grass species, is known to compensate for the effects of disturbance by rapid growth rates (Gross et al 2007a). Conversely, characteristics that promote adaptation to low productivity habitats are associated with low palatability (Niemann et al 1992;Perez-Harguindeguy et al 2003), which is a mechanism of resistance to defoliation, as defined by Briske (1996). Therefore, chemical composition traits (e.g.…”
Section: Grass Strategies To Tolerate or Compensate For Cutting/largementioning
confidence: 99%